Self-bougienage of oesophageal stricture by an 8-year-old child - Carsten Mueller; Winfried Barthlen; Peer Wildbrett (Wolters Kluwer Medknow Publications, 2012)
Oesophageal corrosive injuries have a high potential to result in stricture formation with the requirement for repeat oesophageal dilation. Especially in children, oesophageal bougienage is performed under general anaesthesia or strong sedation. In developing countries without comprehensive medical care, this service might not be available. We report the case of daily oesophageal self-bougienage performed by an 8-year-old Afghan child as highly effective treatment of recurrent oesophageal stricture formation after caustic substance ingestion.